Severe underquantification of HIV-1 group O isolates by major commercial PCR-based assays - Berger, Annemarie; Muenchhoff, M.; Hourfar, K.; Kortenbusch, M.; Ambiel, I.; Stegmann, L.; Heim, A.; Sarrazin, C.; Ehret, R.; Daniel, Volker; Wasner, M.; Plantier, J. -C.; et al. (Clinical microbiology and infection, 2020)
HIV-1 diversity poses major challenges to viral load assays because genetic polymorphisms can impede nucleic acid detection. In addition to the on-going viral diversification within the HIV-1 group M pandemic, HIV-1 genetic diversity is further increased by non-group M infections, such as HIV-1 groups O (HIV-1-O), N and P. We here conducted a systematic evaluation of commercially available PCR assays to detect HIV-1-O isolates. We collected 25 primary HIV-1-O isolates covering all genetic clusters within HIV-1-O. Subsequently, this panel of isolates was tested on eight commercially available quantitative and five qualitative HIV-1 PCR-based assays in serial dilutions. Sequence analyses were performed for severe cases of underquantification or lack of detection. We observed differences between the assays in quantification that depended on the HIV-1-O isolate’s subgroup. All three tested HIV-1-O subgroup IV isolates were underquantified by the Roche CAP/CTM >800-fold compared to the Abbott RealTime assay. In contrast, the latter assay underquantified several subgroup I isolates >200-fold. Notably, the Xpert HIV-1 Viral Load test from Cepheid failed to detect two of the HIV-1-O isolates, whereas the Roche Cobas 8800 assay readily detected all isolates. Comparative sequence analyses identified polymorphisms in the HIV-1-O long-terminal repeat and integrase genes that likely underlie inadequate nucleic acid amplification. Potential viral load underquantification should be considered in therapeutic monitoring of HIV-1-O-infected patients. Pre-clinical assessments of HIV-1 diagnostic assays could be harmonized by establishing improved and internationally standardized panels of HIV-1 isolates that cover the dynamic diversity of circulating HIV-1 strains.
Gesehen am 11.02.2021